Friends from the Future: A Scoping Review of Research into Robots and Computer Agents to Combat Loneliness in Older People - Gasteiger N (Dove Medical Press, 2021)
Norina Gasteiger,1,2 Kate Loveys,1 Mikaela Law,1 Elizabeth Broadbent1 1Department of Psychological Medicine, The University of Auckland, Auckland, New Zealand; 2School of Health Sciences, The University of Manchester, Manchester, UKCorrespondence: Elizabeth BroadbentThe University of Auckland, Building 507, 28 Park Avenue, Grafton, Auckland, 1023, New ZealandTel +64 9 923 6756Email e.broadbent@auckland.ac.nzBackground and Aim: Loneliness is a common problem in older adults and contributes to poor health. This scoping review aimed to synthesize and report evidence on the effectiveness of interventions using social robots or computer agents to reduce loneliness in older adults and to explore intervention strategies.Methods: The review adhered to the Arksey and O’Malley process for conducting scoping reviews. The SCOPUS, PUBMED, Web of Science, EMBASE, CINAHL, PsycINFO, ACM Digital Library and IEEE Xplore databases were searched in November, 2020. A two-step selection process identified eligible research. Information was extracted from papers and entered into an Excel coding sheet and summarised. Quality assessments were conducted using the Mixed Methods Appraisal Tool.Results: Twenty-nine studies were included, of which most were of moderate to high quality. Eighteen were observational and 11 were experimental. Twenty-four used robots, four used computer agents and one study used both. The majority of results showed that robots or computer agents positively impacted at least one loneliness outcome measure. Some unintended negative consequences on social outcomes were reported, such as sadness when the robot was removed. Overall, the interventions helped to combat loneliness by acting as a direct companion (69%), a catalyst for social interaction (41%), facilitating remote communication with others (10%) and reminding users of upcoming social engagements (3%).Conclusion: Evidence to date suggests that robots can help combat loneliness in older adults, but there is insufficient research on computer agents. Common strategies for reducing loneliness include direct companionship and enabling social interactions. Future research could investigate other strategies used in human interventions (eg, addressing maladaptive social cognition and improving social skills), and the effects of design features on efficacy. It is recommended that more robust experimental and mixed methods research be conducted, using a combination of validated self-report, observational, and interview measures of loneliness.Keywords: robots, embodied conversational agents, computer agents, older adults, loneliness, review